Evaluating the effects of time-restricted eating on overweight and obese women with polycystic ovary syndrome: A randomized controlled trial study protocol. - Hui Liu; Fuliang Shangguan; Fen Liu; Yu Guo; Huixi Yu; Hanbing Li; Yinhua Su; Zhongyu Li (PLoS ONE)
Background Time-restricted eating (TRE) manages weight effectively, but choosing how long and what time window remain debatable. Although an 8:00 a.m. to 16:00 p.m. time frame is reported to show positive results in most weight loss trial, its safety and efficacy in overweight and obese women with polycystic ovary syndrome (PCOS) is uncertain. This randomized controlled trial is conducted to evaluate the safety and efficacy of TRE in specific populations. Objective This study aims to assess the 6-month effects of TRE on weight change, metabolic improvement, reproductive recovery, and health-related quality of life in overweight and obese women with polycystic ovary syndrome (PCOS), compared to those who did not receive TRE. Methods This randomized controlled trial will enroll 96 overweight and obese women with polycystic ovary syndrome (PCOS), who will be randomly assigned to either a TRE group (with an eating window from 8:00 a.m. to 16:00 p.m.) or a control group (without eating time restrictions), with 49 participants in each group. Evaluators and data analysts will remain blinded to group allocation throughout the study. The primary outcomes, including changes in weight and body mass index (BMI), will be assessed weekly. Secondary outcomes, encompassing alterations in sex hormones, metabolic parameters, body composition, sleep quality, quality of life, anxiety, and depression, will be evaluated monthly. Compliance and safety will be continuously monitored throughout the study. Additionally, a 6-month follow-up will be conducted at the end of the trial to assess the long-term effects of TRE. Statistical analysis will include the Anderson-Darling test for normality, T-test/Wilcoxon test based on distribution, mixed-effects models for assessing time/group effects, Cox model for time-to-event analysis, repeated ANOVA for change analysis, and sensitivity analysis. All tests will be conducted using appropriate software, with a significance level set at P<0.05. Missing data will be imputed. Discussion The purpose of this study protocol is to further evaluate the effects of TRE in overweight and obese women with PCOS through a randomized controlled trial (RCT). Findings from this study are expected to provide new dietary intervention strategies for overweight and obese PCOS participants. Ethics and dissemination This study has received ethics approval from the Medical Ethics Committee of the University of South China (Number: NHHL027). Participants are included after signing informed consent. Results will be submitted for publication in peer-reviewed journals. Trail registration Trail registration number: ChiCTR2400086815.